Effectiveness of Travel Online Community - Dencheva, Silvena (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2016)
Measuring the effectiveness of online community is a very crucial problem for the community managers. Effectiveness as economic category is measured in reaching certain results and comparing them with the target. In the paper we have aimed at creating methodic for measuring the effectiveness of the travel virtual community. In this regard, we offer methodic that can be adapted to the specific of the business and the strategy of the organization.